Professional javascript for web developers - Zakas, Nicholas C. (Wrox professional guides, 2012)
A significant update to a bestselling JavaScript book As the key scripting language for the web, JavaScript is supported by every modern web browser and allows developers to create client-side scripts that take advantage of features such as animating the canvas tag and enabling client-side storage and application caches